ESCALATING WORK ETHIC AND OPTIMALIZATION FOR EMPLOYEES AND TEACHERS OF BIMBINGAN TERPADU 8 IN PEKANBARU - Ratna Nurani Ratna; Ade Ria Nirmala; Umi Rachmah Damayanti (Yayasan Azam Insan Cendikia, 2022)
Work ethics is a set of positive behaviour and the fondation includes motivation stimulus; main characteristics; primary of passion; fundamental idea; ethic code; moral code; attitude; aspiration; belief; principles; and standard (Sinamo, Darodjat ; 2015:77). Work ethics is a mirror of disciplinary, passionate, and productivity of employees. Employees with low work ethic are possible to have as low as their productivity, vice versa. Work optimalization is a process of work performance according to company standard and supporting the company goal. For implementation, there are several studies to learn some key factors in order to be exxellent in employees work optimalization. All participants are employees in Bimbingan terp@du 8 Pekanbaru and several teacher from different school in Pekanbaru. Participants were provided with disciplinary principal of work ethic and work optimalization materials, how to be a perfect role model employee. The implementation of this community services showed positive respond proven by the enthusiasm of all participants during the event and the QnA session. During this activity, the servants also get feedback on what should be done if they are in a position as a leader. Optimization The implementation of work in a company or organization must be supported by both parties, leaders and employees/members.